Sucrose preferentially promotes expression of OsWRKY7 and OsPR10a to enhance defense response to blast fungus in rice - Tun, Win; Yoon, Jinmi; Vo, Kieu Thi Xuan; Cho, Lae-Hyeon; Hoang, Trung Viet; Peng, Xin; Kim, Eui-Jung; Win, Kay Tha Ye Soe; Lee, Sang-Won; Jung, Ki-Hong; Jeon, Jong-Seong; An, Gynheung (Frontiers in Plant Science, 2023)
Sucrose controls various developmental and metabolic processes in plants. It also functions as a signaling molecule in the synthesis of carbohydrates, storage proteins, and anthocyanins, as well as in floral induction and defense response. We found that sucrose preferentially induced OsWRKY7, whereas other sugars (such as mannitol, glucose, fructose, galactose, and maltose) did not have the same effect. A hexokinase inhibitor mannoheptulose did not block the effect of sucrose, which is consequently thought to function directly. MG132 inhibited sucrose induction, suggesting that a repressor upstream of OsWRKY7 is degraded by the 26S proteasome pathway. The 3-kb promoter sequence of OsWRKY7 was preferentially induced by sucrose in the luciferase system. Knockout mutants of OsWRKY7 were more sensitive to the rice blast fungus Magnaporthe oryzae, whereas the overexpression of OsWRKY7 enhanced the resistance, indicating that this gene is a positive regulator in the plant defense against this pathogen. The luciferase activity driven by the OsPR10a promoter was induced by OsWRKY7 and this transcription factor bound to the promoter region of OsPR10a, suggesting that OsWRKY7 directly controls the expression of OsPR10a. We conclude that sucrose promotes the transcript level of OsWRKY7, thereby increasing the expression of OsPR10a for the defense response in rice.